2012
DOI: 10.1111/j.1743-6109.2012.02953.x
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Seeking Medical Help in Patients with New-Onset Erectile Dysfunction Remained High Over and Despite the PDE5 Era—An Ecological Study

Abstract: Introduction It is common knowledge among researchers that erectile dysfunction (ED) is an important sentinel marker of cardiovascular and overall men’s health. Aim Determine whether the delay of time between ED onset and seeking medical help (DSH), considered as a proxy of awareness of the importance of ED for overall men’s health, has shortened during the phosphodiesterase type 5 inhibitors (PDE5) era. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
1
19
1
Order By: Relevance
“…Only approximately half of our men had a high household income, so some financial barriers might deter them from seeking and obtaining the desired medical attention. The mean time between noticing ED and taking the first treatment was 4.3 months, which was shorter than in the Salonia et al 9. study, which had a mean time of 30.2 months (median 12.0; range 5–300 months).…”
Section: Discussionmentioning
confidence: 56%
“…Only approximately half of our men had a high household income, so some financial barriers might deter them from seeking and obtaining the desired medical attention. The mean time between noticing ED and taking the first treatment was 4.3 months, which was shorter than in the Salonia et al 9. study, which had a mean time of 30.2 months (median 12.0; range 5–300 months).…”
Section: Discussionmentioning
confidence: 56%
“…Numerous researches revealed that men with ED find it difficult to report their conditions to doctors,1516 although all men from a cross-national survey agreed that ED was a source of great dismal for themselves and their partners, and nearly all disagreed that they were too old for sex 17. To begin with, more than half of those who were screened ED positive did not in fact think that they had ED 18.…”
Section: Introductionmentioning
confidence: 99%
“…A significant time delay often exists between the onset of ED symptoms and both presenting to a clinician to discuss the symptoms and instituting treatment. Salonia et al 22 reported on 619 patients seeking medical help for new-onset ED in the PDE5i era, where the mean delay prior to presentation was 30.2 months (median 12.0; range 5-300). This delay seems surprising given the likely waning of the taboo associated with openly discussing ED, as well as the explosion of direct-to-consumer advertising for ED treatments in both electronic and print media 25 .…”
Section: Discussionmentioning
confidence: 98%
“…Notably, this approach does not contradict any ED management guidelines, as no urological society mandates a trial of non-surgical ED therapies prior to proceeding with PPI. This decision may facilitate earlier restoration of erectile function with a treatment option that affords high satisfaction 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation